Ewolucja celów polskiego prawa zamówień publicznych od okresu międzywojennego do współczesności - Stawiński, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article presents the evolution of the objectives of public procurement law in Poland from interwar period to present-day. Especially, the article shows an important influence of European Union legislation on the legal regulation of public procurement and its objectives.
Keywords: public procurement law; objectives of public procurement law; evolution of public procurement law; European Union; directives